Influence of the positions of thiophenes and side chains on diketopyrrolopyrrole based narrow band-gap small molecules for organic solar cells. (October 2016) - Zhao, Yuan; Zhou, Xue; Wu, Kailong; Wang, Huan; Qu, Shiwei; He, Feng; Yang, Chuluo
Abstract: A series of low band-gap small molecules with multiple donor-acceptor type backbones, which contained diketopyrrolopyrrole as a bulk core, thiophene/benzene as donor moiety and isoindigo/thienoisoindigo as end acceptor moiety, were designed and synthesized. All the four compounds show broad absorption from 300 nm to 900 nm and the optical band gaps are all lower than 1.5 eV. The absorption spectra and the energy levels of the four compounds are finely tuned by changing the donor unit of benzene with thiophene. X-ray diffraction measurement indicated that there are differences between the crystallinity of the four materials. The effects of the positions of thiophenes and side chains on morphology, charge transport and photovoltaic properties of these narrow band-gap small molecules were also studied. The highest power conversion efficiency of these compounds is 2.01% after thermal annealing. Ternary solar cells were fabricated to investigate the effect of the second donor on the power conversion efficiency. Graphical abstract: Highlights: Four narrow band-gap small molecules were synthesized and characterized. The positions of thiophenes and side chains have great effects on crystallinity, charge carrier mobility and morphology. The devices based on DPPTTC8 shows the highest power conversion efficiency. The power conversion efficiency of DPPTTC6 based devices were improved from 1.06% to 3.78% by using ternary solar cells.